Hubungan Antara Beban Kerja dan Kompetensi Terhadap Komitmen Karyawan: The Relationship Between Workload and Competency on Employee Commitment - Yudi Wahyudin Suwandi; Atep Iyan; Imas Komariyah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
This study examines the individual and combined effects of workload and competency on employee commitment within the Business Unit of Building a Prosperous Family Economy in Bandung Regional 1 (PNM Cimahi Branch). Workload and competency are pivotal factors that can significantly influence employee commitment, particularly in demanding work environments. A quantitative approach was employed, gathering primary data via surveys from 248 employees at the PNM Cimahi Branch. The collected data included measurements of employee workload, competency levels, and commitment to the organization. Path analysis was utilized to assess the relationships between these variables. The findings indicate that both workload and competency positively influence employee commitment, both individually and when considered together.